Development of ovine chorionic somatomammotropin hormone-deficient pregnancies - Baker, Callie M. (Am J Physiol Regul Integr Comp Physiol, 2016)
Intrauterine growth restriction (IUGR) is a leading cause of neonatal mortality and morbidity. Chorionic somatomammotropin hormone (CSH), a placenta-specific secretory product found at high concentrations in maternal and fetal circulation throughout gestation, is significantly reduced in human and sheep IUGR pregnancies. The objective of this study was to knock down ovine CSH (oCSH) expression in vivo using lentiviral-mediated short-hairpin RNA to test the hypothesis that oCSH deficiency would result in IUGR of near-term fetal lambs. Three different lentiviral oCSH-targeting constructs were used and compared with pregnancies (n = 8) generated with a scrambled control (SC) lentiviral construct. Pregnancies were harvested at 135 days of gestation. The most effective targeting sequence, “target 6” (tg6; n = 8), yielded pregnancies with significant reductions (P ≤ 0.05) in oCSH mRNA (50%) and protein (38%) concentrations, as well as significant reductions (P ≤ 0.05) in placental (52%) and fetal (32%) weights compared with the SC pregnancies. Fetal liver weights were reduced 41% (P ≤ 0.05), yet fetal liver insulin-like growth factor-I (oIGF1) and -II mRNA concentrations were reduced (P ≤ 0.05) 82 and 71%, respectively, and umbilical artery oIGF1 concentrations were reduced 62% (P ≤ 0.05) in tg6 pregnancies. Additionally, fetal liver oIGF-binding protein (oIGFBP) 2 and oIGFBP3 mRNA concentrations were reduced (P ≤ 0.05), whereas fetal liver oIGFBP1 mRNA concentration was not impacted nor was maternal liver oIGF and oIGFBP mRNA concentrations or uterine artery oIGF1 concentrations (P ≥ 0.10). Based on our results, it appears that oCSH deficiency does result in IUGR, by impacting placental development as well as fetal liver development and function.